An appraisal of the effectiveness of nature‐close torrent control methods – Jindrichovicky Brook case study. Issue 5 (11th December 2013) - Kovar, Pavel; Krovak, Frantisek; Rous, Vit; Bily, Michal; Salek, Miroslav; Vassova, Darina; Hrabalikova, Michaela; Tejnecky, Vaclav; Drabek, Ondrej; Bazatova, Tereza; Peskova, Jitka
ABSTRACT Discharge fluctuation and extreme bed load movement, i.e. erosion and sedimentation occurring on short upper reaches of the river, are characteristic features of torrential rivers. This paper presents a biotechnical appraisal of a torrent catchment for implementing revetments methods, focusing on selected hydraulic characteristics of the flow. The Infiltration and Kinematic wave hydrological model (KINFIL) hydrological model (for design discharges) is used to verify these variables and also the Hydrologic Engineering Centre's River Analysis System and Sedimentation and River Hydraulics Two‐Dimensional hydraulic models for channel flow. Data and computation for proposing nature‐close remedial measures are demonstrated in a case study of the Jindrichovicky Brook, a mountain torrent located in the Ore Mountains (Czech Republic). Particular attention is given to appropriate adaptation of the river for the invertebrate community. The hydraulic analysis is carried out in two sections of the river (section A: 'nature‐close', restored in 2008, and section B: 'old style', regulated in the 1970s). The aim is to compute the major hydraulic characteristics (depths, velocities, shear stress values etc.). Then, a hydrobiological investigation is carried out in both sections to find how much the invertebrate communities extended their diversity and abundance as a consequence of better geomorphological diversity after restoration. It was found that, from the hydraulic point of view, the old section B is sufficiently robust and stable. However, it is clearly evident that this section can hardly be populated by fauna and if so, then only very sparsely and impermanently. Section A meets both priorities, hydraulic stability and an acceptable living environment for the benthic community. Copyright © 2013 John Wiley & Sons, Ltd.